Opioid Tolerance and Physical Dependence: Role of Spinal Neuropeptides, Excitatory Amino Acids and Their Messengers. (1st March 2000) - Jhamandas, Khem; Powell, Kelly; Quirion, Remi; Milne, B
Abstract : Chronic opioid treatment results in the development of tolerance and physical dependence. The mechanisms underlying opioid tolerance and/or physical dependence are unclear. Recent studies suggest that opioid receptor or nociceptive, neural network-based adaptations contribute to this phenomenon. At the spinal level, the genesis of tolerance and physical dependence is associated with increased excitatory amino acid activity expressed through N -methyl-D-aspartate receptors in the dorsal horn. However, recent evidence also implicates spinal neuropeptide transmitters such as calcitonin gene-related peptide (CGRP) and substance P in the development of opioid tolerance. Long term spinal morphine treatment increases CGRP-like immunostaining in the dorsal horn, and coadministration of morphine with CGRP8-37, a competitive CGRP1 receptor antagonist, prevents this response as well as loss of the analgesic potency. CGRP8-37, like N -methyl-D-aspartate receptor antagonists, has the potential to restore morphine potency in experimental animals who are already tolerant to the opioid agonist. Recent evidence suggests that the effects of excitatory amino acid and neuropeptide receptor activity may be expressed through the generation of messengers such as nitric oxide and prostanoids. Agents that inhibit the synthesis of nitric oxide and prostanoids have the potential to inhibit and reverse spinal opioid tolerance, suggesting that this phenomenon may be expressed through the activity of these mediators. Nociceptive transmission in the dorsal horn of the spinal cord also involves activity of a number of other mediators including morphine modulatory neuropeptides, neuropeptide FF and neuropeptide SF. The role of these mediators and their relationship with other factors implicated in tolerance remain to be determined.